Statistical analysis of wastewater monitoring for maximum peak factor estimation (2021)
The design and operation of sanitary sewerage systems are based on the knowledge of peak and the average daily wastewater flows. The maximum peak factor is obtained through the ratio of the maximum flow and the average discharge flow of wastewater generated in a system. In this sense, the maximum peak factor was estimated by monitoring wastewater flow in an urban sector of the city of San José de Cúcuta, Colombia. This urban sector represents 45.6% of the sanitary sewerage of the city. Stochastic modeling of the peak flow was performed, and a mathematical model was constructed to estimate the maximum peak factor using a correlational study using statistical methodology. Through linear regression analysis, a model was obtained that estimates the value of the maximum peaking factor based on knowledge of the average daily wastewater flow. The results indicate that the model is potential, and the expression is statistically significant and satisfies the assumptions established for the classical linear regression model.